Engaging the Guatemala Scientific Diaspora: The Power of Networking and Shared Learning - Bonilla, Kleinsy; Romero-Oliva, Claudia S.; Arrechea, Susana; Ortiz Osejo, Nereyda Y.; Mazariegos, Sofia; Alonzo, Margarita; Orellana-Corrales, Gabriela; del Valle, Andrea C.; Montenegro-Bethancourt, Gabriela (Frontiers in Research Metrics and Analytics, 2022)
The underdevelopment of the higher education system in Guatemala and the fragility of its science and technology (S&T) contexts have compelled an increasing number of talented Guatemalan scientists to be trained, educated, and employed abroad. The relocation of such skilled human power to different countries and regions has resulted in a growing Guatemalan Scientific Diaspora (GSD). Until recently, the emigration of scientists from the Global South to scientifically advanced countries in the North was studied as it negatively impacted the countries of origin. However, technological upgrades and globalization have progressively shifted the paradigm in which such scientific diasporas interact and connect, thus enabling them to influence their home countries positively. Due to the lack of knowledge-based evidence and functioning connecting platforms, the value and potential of the GSD in their involvement in proposing solutions to complex socio-economic, environmental, and other challenges faced by Guatemalan society remain unknown. Moreover, the lack of interaction of relevant stakeholders (S&T policy agents, international partners, higher education institutions and research centers, industry, and relevant not governmental organizations) represents a pervasive obstacle to the untapped impact of the GSD in the country. This study outlines the Guatemalan scientific diasporas’ networking as a mechanism for building research excellence and intellectual capital. This force could respond to the need to strengthen the national science capacities and meet the demands for knowledge production and access to broader sectors of society. This research applied qualitative methodology that, through the conduction of focus group discussions and semi-structured interviews with members of the Guatemalan scientific community and relevant key stakeholders, delved into the existence and articulation of the GSD and potential stages for their engagement with their country of origin. Findings highlight the importance of digital and technological pathways that might leverage the GSD’s knowledge and experience, channeling skills, and international connections for better interaction with the Guatemalan society. Furthermore, the discussion addresses how technology might turn brain drain into brain circulation, enabling the articulation of the GSD as a viable opportunity to generate collaboration between scientists abroad and local actors, ultimately impacting the development of Guatemalan science and national research capacities.